ASSOCIATION OF RISK FACTORS WITH SPONTANEOUS PRETERM LABOUR WITH INTACT FOETAL MEMBRANES - Zaman, Uzma; Nazir, Aamir; Taimoor, Alruba; Shah, Inayat; Fatima, Sadia; Jadoon, Humaira (Journal of Ayub Medical College Abbottabad, 2019)
Background: Spontaneous preterm labour refers to the onset of uterine contractions of sufficient strength and frequency to effect progressive dilatation between 24 and 37 weeks of gestation. The objective of the study was to determine an association between risk factors and spontaneous preterm labour with intact foetal membranes. Methods: A case control study was designed which was conducted in the Department of Obstetrics and Gynaecology, Ayub Teaching Hospital, Abbottabad. Sample size of 262 subjects was equally divided into two equal groups (131 cases and control each). Non-probability consecutive sampling was used collection of samples. Pregnant women presenting after 24 weeks of gestation with spontaneous preterm labour with intact membranes were considered as cases. While, pregnant women presenting after 37 complete weeks of gestation with normal pregnancy were considered as controls. The diagnosis of bacterial vaginosis was established by Amsel criteria. Asymptomatic bacteriuria was diagnosed by microscopy. Odds ratios were calculated as measure of association with calculation at 95% confidence interval. Level of 5% (p<0.05) was used to test for significant difference. Results: Mean±SD age of cases was 26.97±7.072. Subjects with young maternal age (<20 years) were 27 (10.3%) from cases and 12 (4.6%) from controls (OR=2.575, 95% CI: 1.242, 5.338). The subjects with advanced maternal age (>35 years) were 26 (9.9%) from cases and 15 (5.7%) from controls (OR=0.522, 95% CI: 0.262, 1.039). 25 (19.1%) cases and 6 (4.6%) controls had bacterial vaginosis (OR=4.914, 95% CI: 1.943, 12.426). Asymptomatic bacteriuria was present in 03 (2.3%) subjects from cases and 2 (1.5%) from controls (OR=1.512, 95% CI: 0.248, 9.199). Conclusion: The study concluded that risk factors like young maternal age and bacterial vaginosis are significantly associated with spontaneous preterm labour with intact foetal membranes. While, association of other risk factors like advanced maternal age and asymptomatic bacteriuria with spontaneous preterm labour is still debatable. Keywords: Spontaneous preterm labour; intact foetal membranes; risk factors